Social media portfolio : Maria Lula Kookies project / Eszrul Anuar Eshkak - Eshkak, Eszrul Anuar (2018)
Maria Lula Kookies Project is start its online business operation in year 2016. It is equally owned and managed by its two partners Pn Maria Fida Binti Ismail and En Eszrul Anuar Eshkak. Maria Lula Kookies Project is a food and beverages business. The business is focusing on selling cookies and cake online. The transactions are open to all group of customers. Maria Lula Kookies Project not only focusing around the market but also offer customers who are outside or different regions or states. By using Facebook platform, the product market is more open. With an increasingly modern marketing form and product design that needs to be updated regularly, we offer high quality services to our customers through this virtual platform. Maria Lula Kookies Project intends to hire the agents to handle customer service and delivery the product.